MEMBANGUN KARAKTER ISLAMI PADA ANAK USIA DINI MELALUI PENDIDIKAN AGAMA YANG HOLISTIK - Aldi, Muhammad; Khairanis, Retisfa (Pijar Pelita: Journal of Early Childhood Education and Early Childhood Islamic Education, 2025)
This study aims to examine the role of Islamic religious education in building Islamic character in early childhood through a holistic approach. Early childhood is at an important stage of development in the formation of moral and spiritual values, so that comprehensive religious education becomes the foundation for instilling a strong Islamic character. The focus of this research is to identify effective strategies that can be applied in learning Islam in the family, school and community environments. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with educators, parents, and observers of early childhood education, as well as direct observation of Islamic learning practices in several early childhood education institutions. Data analysis was conducted using the triangulation method to ensure the validity and reliability of the results. The results show that holistic Islamic religious learning, involving integration between cognitive, affective and psychomotor aspects, is able to effectively shape Islamic character in early childhood. Strategies such as the use of play while learning methods, Islamic stories, simple worship practices, and strengthening Islamic values in daily interactions are proven to increase children's religious understanding and positive behavior. The implications of this research show the importance of collaboration between parents, teachers and the social environment in building children's Islamic character from an early age. This research contributes to the development of Islamic learning methods that are more relevant to the developmental needs of early childhood, as well as providing practical guidance for educators and policy makers in designing effective Islamic character education programs.  Keywords: Islamic Character, Early Childhood, Religious Education, Holistic